Measurements of 14CH4 and 14CO in ice from Taylor Glacier: Last Deglaciation and Deep Core Results ... - Petrenko, Vasilii (U.S. Antarctic Program (USAP) Data Center, 2018)
This data set contains measurements of 14CH4 and 14CO in ice cores from Taylor Glacier, Antarctica. This includes measurements in ice from the last deglaciation (18 - 8 kyr), for the purposes of paleoatmospheric 14CH4 reconstruction. The data set also includes measurements in older ice (50 - 70 kyr) from a deep ice core, made for the purposes of studying in situ cosmogenic 14C production in ice. All data are in excel format. ...